2014
DOI: 10.1177/0265659014537508
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of an in-service education program on promoting language development in young children: A pilot study with early childhood educators

Abstract: Early childhood educators (ECEs) play an important role in fostering language development in young children. In-service education, led by speech-language pathologists (SLPs), has a potential role in educating ECEs about language development. In this pilot study, 42 ECEs attended an in-service education program and completed pre- and post-questionnaires to explore their perceptions of the impact of the in-service on their knowledge of child language development and language-promoting strategies and their confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
4
25
0
3
Order By: Relevance
“…Research has demonstrated positive outcomes among educators working in countries that have similar characteristics to Australia, including Canada, the USA and Ireland (Cabell, Justice, McGinty, DeCoster & Forston, 2015). Pilot research in Australia has shown promising improvements in educators practice following the LLLI program (Scarinci, Rose, Pee, & Webb, 2014).…”
Section: The Every Toddler Talking Initiativementioning
confidence: 99%
“…Research has demonstrated positive outcomes among educators working in countries that have similar characteristics to Australia, including Canada, the USA and Ireland (Cabell, Justice, McGinty, DeCoster & Forston, 2015). Pilot research in Australia has shown promising improvements in educators practice following the LLLI program (Scarinci, Rose, Pee, & Webb, 2014).…”
Section: The Every Toddler Talking Initiativementioning
confidence: 99%
“…The CoS early intervention program (Marvin et al, 2002) (Berthelsen & Brownlee, 2007;Dalli et al, 2011;Rockel, 2009), using relationships as a tool to support children's learning and development via shared responsive, consistent communications (Brebner et al, 2015;Elfer & Page, 2015;French, 2013). In essence, frames like the CoS also become a way for educators to effectively describe and apply understandings of their early communication to a lack of confidence in and knowledge to support delays or disorders in this arena (Letts & Hall, 2003;Mroz, 2006;Scarinci et al, 2014). Only when such professional development and training was put into a relational context did children show improvement in their communications and patterns of talk (Brebner et al, 2015;Cherrington, 2012;Elfer & Page, 2015;Macfarlane et al, 2015;Rhyner et al, 2012).…”
Section: [Hl2] Between Family and Childmentioning
confidence: 99%
“…A small body of research has been conducted by speech and language experts in the health sciences to understand the professional knowledge, confidence and practices that educators bring to their work in fostering young children's language development. Using combinations of pre-and post-professional development training questionnaires, semi-structured interviews and/or observational data of educators' on-floor work with children, studies suggest that educators have limited time to devote to speech and language development, disorders and pedagogy training which affects their confidence in this work with young children (Letts & Hall, 2003;Mroz, 2006;Scarinci, Rose, Pee & Webb, 2014). Alarmingly, research in this area also indicated a distinct disconnect between the knowledge gains educators reported regarding young children's speech and language development following such training, with this knowledge not typically translating to their work with the children in their care (Cunningham et al, 2009;Piasta et al, 2012;Scarinci et al, 2014).…”
Section: Non-education Researcher's Perspectives: Gaps In Knowledge Amentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies also seek to understand how teaching professionals perceive the role of their teaching in all the language development process (Cash, Cabell, Group counselling collaboration model In this study, we designed and implemented a collaborative counselling process focused on promoting changes in the way three teaching professionals understood their work in the area of communication and language in a special school classroom. This was inspired by previous training programs for teachers, such as the 'Learning Language and Loving It' program created by Weitzman and Greenberg (2002) and other programs adapted from it (Cabell et al, 2011;Flowers, Girolametto, Weitzman & Greenberg, 2007;Girolametto, Weitzman, Lefebvre & Greenberg, 2007;McDonald et al, 2015;Piasta et al, 2012;Scarinci, Rose, Pee & Webb, 2015;Weitzman et al, 2006).…”
mentioning
confidence: 99%